Evaluation of Internal Adaptation of Different CAD/CAM Endocrown Materials: A Comparative Microcomputed Tomography Study - Wala Saad; Abdul Rahman Saleh; Manal Almaslamani (Ceramics, 2025)
Objective: The purpose of this investigation was to assess and compare the internal adaptation of different distinct CAD (Computer-aided design)/CAM (Computer-aided manufacturing) endocrown materials: feldspathic porcelain, indirect composite, hybrid ceramic, reinforced lithium disilicate, and lithium disilicate, utilizing microcomputed tomography. Methods: Standardized endocrown restorations were fabricated for mandibular first molar models. A total of seventy-five restorations were evenly allocated into five groups (n = 15 each): Group I (Cerec Blocks), Group II (Lava Ultimate), Group III (PICN Vita Enamic), Group IV (Celtra Duo), and Group V (Cerec Tessera). The restorations were bonded using PANAVIA V5 adhesive resin cement. To evaluate internal adaptations within the restorations, three distinct locations were selected for the acquisition of high-resolution micro-CT scans: the margin, the axial wall, and the pulpal floor. Data were analyzed using SPSS. To identify statistically significant differences among groups, a two-way ANOVA was conducted, followed by post hoc Tukey tests. Results: The statistical analysis did not reveal significant differences in internal gap measurements across the various material groups (p = 0.055). However, significant variations were observed within individual material groups (p < 0.001) at distinct locations, with the most pronounced discrepancies in thickness evident at the pulpal floor. Conclusion: While no significant differences were observed in internal adaptations among the various endocrown materials, substantial intra-group variability, particularly in terms of pulpal floor thickness, was evident. Since the study maintained a consistent preparation design across all groups, the observed variations in internal adaptation are likely attributed to differences in material behavior rather than changes in preparation geometry.